Mapping the implementation characteristics of new Medicine programs in Brazilian federal universities - Cyrino, Eliana Goldfarb [UNESP]; Lemes de Sordi, Mara Regina; Cavalcanti Vaz Mendes, Geisa do Socorro; Luna, Willian Fernandes; Mendonca, Carolina Siqueira [UNESP]; Fronza Alexandre, Fabiola Lucy; Vitti Junior, Walter [UNESP]; Godoy, Daniele Cristina [UNESP]; Parenti, Luciana Cristina [UNESP]; Miranda Lopes, Cesar Vinicius; Silva, Evellin Bezerra da; Bruni Fruet de Freitas, Maria Silvia; et al. (Pan Amer Health Organization, 2020)
Objective. To map the implementation characteristics of Medicine programs established in Brazilian federal universities from 2013 onwards. Methods. A qualitative and quantitative exploratory study was performed. Newly created Medicine programs were identified in federal universities, with analysis of pedagogical frameworks and interviews with students, faculty, and health care professionals from associated health care services. Data were analyzed using qualitative and quantitative methods. Results. Thirty new Medicine programs were identified, of which 24 were visited. All the new programs were located outside large urban centers and capitals, across the five Brazilian macro-regions, and adopted various formative configurations in an attempt to overcome fragmentation of content with active methodologies and formative evaluations. The healthcare network is used for training as a means to meet the challenge of academic-health service-community integration, with the aim of providing critical education focused on public health. The establishment of the Medicine programs facilitated to a limited extent the retention of faculty in remote areas and promoted the access of local students and the creation of residency programs, which are powerful strategies to enhance the retention of medical professionals. Conclusions. Variations were observed among the programs in the manner of implementation and adherence to the National Curriculum Guidelines for Medicine, published in 2014. The construction of medical training models that appropriately address local specificities and the requirements of the Unified Health System in its formative role for health care may contribute to reduce health inequalities.
Keywords: Education; medical; health consortia; education; undergraduate; higher education institutions; public health; Brazil